The cost of banking services and the technical efficiency of a South African bank - Gert J van der WSesthuizen; Chris van Heerden (The Journal for Transdisciplinary Research in Southern Africa, 2008)
Does the performance of one of the four largest banks in South Africa justify the customers’ complaints about the higher bank fees? Data Envelopment Analysis (DEA) was used to estimate the technical efficiency and returns to scale of one of the largest banks in South Africa. The intermediation approach was applied to classify the inputs and outputs and the analyses were conducted with both input- and output- orientation under variable returns to scale. Returns to scale efficiency and technical efficiency for 37 districts over a period of 22 months were estimated. The analyses indicated that 19 districts out of the 37 districts were never fully technically efficient during the 22 months (input- and output-orientated). It appears that customers’ complaints about high service fees are justified.